Harnessing structure-activity relationship to engineer a cisplatin nanoparticle for enhanced antitumor efficacy - Paraskar, Abhimanyu S.; Soni, Shivani; Chin, Kenneth T.; Chaudhuri, Padmaparna; Muto, Katherine W.; Berkowitz, Julia; Handlogten, Michael W.; Alves, Nathan J.; Bilgicer, Basar; Dinulescu, Daniela M.; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cisplatin is a first line chemotherapy for most types of cancer. However, its use is dose-limited due to severe nephrotoxicity. Here we report the rational engineering of a novel nanoplatinate inspired by the mechanisms underlying cisplatin bioactivation. We engineered a novel polymer, glucosamine-functionalized polyisobutylene-maleic acid, where platinum (Pt) can be complexed to the monomeric units using a monocarboxylato and an O –> Pt coordinate bond. We show that at a unique platinum to polymer ratio, this complex self-assembles into a nanoparticle, which releases cisplatin in a pH-dependent manner. The nanoparticles are rapidly internalized into the endolysosomal compartment of cancer cells, and exhibit an IC50 (4.25 + 0.16 mu M) comparable to that of free cisplatin (3.87 +/- 0.37 mu M), and superior to carboplatin (14.75 +/- 0.38 mu M). The nanoparticles exhibited significantly improved antitumor efficacy in terms of tumor growth delay in breast and lung cancers and tumor regression in a K-ras(LSL/+)/Pten(fl/fl) ovarian cancer model. Furthermore, the nanoparticle treatment resulted in reduced systemic and nephrotoxicity, validated by decreased biodistribution of platinum to the kidney as quantified using inductively coupled plasma spectroscopy. Given the universal need for a better platinate, we anticipate this coupling of nanotechnology and structure-activity relationship to rationally reengineer cisplatin could have a major impact globally in the clinical treatment of cancer.
Keywords: cancer; chemotherapy; nanomedicine